Coaching in Education - Othman, Norasmah (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
Education is one of the most important aspects for everybody lives. It has also been shown to contribute to the long-term gains of individuals, families, and communities, as well as toward the development of nations. Thus, educators should ensure that implementation of the teaching and learning process is effective and appropriate for their students. To this end, educators should engage often in various methods in teaching and learning. Hence, this paper discuss on the current method used in education and the method known as coaching. Finally, this paper provides an overview of coaching; the differences between coaching, mentoring, consultation and consulting; how to coach; principle of coaching; coaching models and what to avoid. Using the structure of this guide as a step-by-step guide may help more teachers/educators to implement coaching in schools.